(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
In forensic studies the composition of ink is used as writing media used in fountain pen, ball point pen, and gel pen, as well as ink used in printed security papers or ink used in merchandise for printing and logos. Certain forensic dispersive microanalysis method. However, they are combined with a complete reflection technique to provide a better level of specificity. Characterization can be done using the SEM-EDS technique.Inorganic elements present in the cellulose matrix of paper can be characterized and identified using the SEM-EDS technique. Ink has a low iron(II) sulphate level, it is less prone to decomposition and provides higher stability on paper, leading to the conclusion that the document can be retained for a longer period of time under certain environmental circumstances.